Answer:
1 and 3
Step-by-step explanation:
We are given that:
f(x) = 2ˣ - 2
g(x) = 3x - 3
We want to get the solution of f(x) = g(x). This means that we want to get the values of x that make the two solutions equal
Since the choices givens all belong to the given table, we can simply get the solution by examining the table and comparing f(x) with g(x) at each value:
At x = -1:
f(x) = -3/2
g(x) = -6
f(-1) is not equal to g(-1)
Therefore, this is not a solution
At x = 0:
f(x) = -1
g(x) = -3
f(0) is not equal to g(0)
Therefore, this is not a solution
At x = 1:
f(x) = 0
g(x) = 0
f(1) is equal to g(1)
Therefore, this is a solution
At x = 2:
f(x) = 2
g(x) = 3
f(2) is not equal to g(2)
Therefore, this is not a solution
At x = 3:
f(x) = 6
g(x) = 6
f(3) is not equal to g(3)
Therefore, this is a solution
At x = 4:
f(x) = 14
g(x) = 9
f(4) is not equal to g(4)
Therefore, this is not a solution
At x = 5:
f(x) = 30
g(x) = 12
f(5) is not equal to g(5)
Therefore, this is not a solution
Based on the above, the only solutions among the given choices are 1 and 3
Hope this helps :)